THE RELATIONSHIP BETWEEN COVID-19 PERCEIVED RISK AND ATTITUDES TOWARDS COVID-19 VACCINATION IN HEALTHCARE PROFESSIONALS: AN EXAMPLE OF EASTERN TURKEY - Sonmez, Tugce; Yarah, Suheyla; Turan, Gulcan Bahcecioglu (Medicinska Naklada, 2021)
Bacground: This study aimed to examine the relationship between COVID-19 perceived risk and attitudes towards COVID-19 vaccination in healthcare professionals. Subjects and methods: This cross-sectional descriptive study included a total of 580 healthcare professionals. Results: The healthcare professionals' COVID-19 Perceived Risk Scale (CPRS) and Attitudes towards COVID-19 Vaccine Scale (ATV-COVID-19) mean scores were 31.3615.16 and 3.0010.61, respectively. A statistically significant negative correlation was found between their CPRS and ATV-COVID-19 mean scores. Conclusions: The healthcare professionals had a high COVID-19 perceived risk and moderately positive attitudes towards COVID-19 vaccine.
Keywords: COVID-19; attitudes towards vaccination; healthcare professionals; perceived risk